p28 Bacterial Peptide, as an Anticancer Agent - Yaghoubi, Atieh; Khazaei, Majid; Avan, Amir; Hasanian, Seyed Mahdi; Cho, William C.; Soleimanpour, Saman (Frontiers in Oncology, 2020)
Cancer remains a major cause of morbidity and mortality irrespective of the type of conventional chemotherapy. Therefore, there is an urgent need for new and effective anticancer therapeutic agents. Bacterial proteins and their derivative peptides appear as a promising approach for cancer treatment. Several, including an amphipathic, α-helical, 28-amino acid peptide derived from azurin, a 128-amino acid copper-containing redox protein secreted from Pseudomonas aeruginosa, show clinical promise in the treatment of adult and pediatric solid tumors. The peptide, p28, is a post-translational, multi-target anticancer agent that preferentially enters a wide variety of solid tumor cells. Mechanistically, after entry, p28 has two major avenues of action. It binds to both wild-type and mutant p53 protein, inhibiting constitutional morphogenic protein 1 (Cop1)-mediated ubiquitination and proteasomal degradation of p53. This results in increased levels of p53, which induce cell-cycle arrest at G2/M and an eventual apoptosis that results in tumor cell shrinkage and death. In addition, p28 also preferentially enters nascent endothelial cells and decreases the phosphorylation of FAK and Akt inhibiting endothelial cell motility and migration. Here, we review the current basic and clinical evidence suggesting the potential of p28 as a cancer therapeutic peptide.